Bāṃlāra mrṯśilpa alaṃkaraṇa : phaṭobhittika śilpa tathya sañcaẏana : ekaṭi kathikā - Mitra, Śambhunātha, 1923- (Śa. Mitra : prāptisthāna Baiśākhī Pābaliśārsa, 1981)
Notes on the development of terra-cotta art in Bengal, specially in temple decoration, since 16th century.